2013
DOI: 10.1002/ptr.5066
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng Attenuates Experimental Colitis in the Azoxymethane/Dextran Sulfate Sodium Mouse Model

Abstract: Patients suffering from inflammatory bowel disease are at a high risk of developing colorectal cancer. To assess the anti-cancer potential of botanicals, in this study, we evaluated the effects of Panax notoginseng on azoxymethane (AOM)/dextran sulfate sodium (DSS)-induced colitis. One week after A/J mice received AOM, the animals received DSS for 8 days, or were supplemented with P. notoginseng extract, at 30 or 90 mg/kg. DSS-induced colitis was scored with the disease activity index (DAI). The severity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
(52 reference statements)
3
17
0
Order By: Relevance
“…Previously, we evaluated the effects of another herb in the ginseng family, notoginseng, on experimental colitis for up to 14 days. We reported that notoginseng attenuated the acute colitis [34] comparable to what was observed using AG in this study. Although the ginseng saponin profiles are different between AG and notoginseng, the two botanicals also share a number of common ginsenosides.…”
Section: Discussionsupporting
confidence: 87%
“…Previously, we evaluated the effects of another herb in the ginseng family, notoginseng, on experimental colitis for up to 14 days. We reported that notoginseng attenuated the acute colitis [34] comparable to what was observed using AG in this study. Although the ginseng saponin profiles are different between AG and notoginseng, the two botanicals also share a number of common ginsenosides.…”
Section: Discussionsupporting
confidence: 87%
“…After the mice were killed under anesthesia, the colons were immediately removed and fixed in 10% buffered formalin, paraffin-embedded, sectioned, and stained with H&E. Histologic score of H&E-stained specimens of the colon was determined by two pathologists in a blinded fashion. Histologic sections were scored using a validated scoring system as described previously (Williams et al, 2001;Wen et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Yunnan is the Chinese largest producer of Panax notoginseng , which accounts for 97% of the production of China, and more than 400 products were made from it by 1302 companies in China. P. notoginseng is a promising candidate in preventing and treating inflammation-associated colon carcinogenesis [ 78 ]. Macroporous resin from the leaves of P. notoginseng is enriched with low polarity PPD group saponins of 85% ethanol fraction, which is a new alternative source of anticancer saponins [ 79 ].…”
Section: The Lowest Cancer Mortality Associated With Anticancer Crmentioning
confidence: 99%